The Stability of Hydro Technical Embankments under Various Seepage Conditions - Adam Balawejder; Mieczyslaw Chalfen; Tadeusz Molski; Andrzej Surowiecki (Communications - Scientific letters of the University of Zilina, 2007)
The flood control devices in Bytom Odrzanski protect the city against the Odra water flooding with a probability p 10 20 %. The flood protection devices (class validity II) of hydro-technical structures are designed and realized for protection improvement and designed on the flow in the Odra river with a probability p 1 % . The earth embankment (2044 total in length) will be built with local non-cohesive grounds. On the 900 m length, the base of the embankment presents no cohesive grounds. It causes conditions for free filtration through the base and body of the embankment. The computer calculations of filtration showed high (locally) hydraulic heads (Imax 0,984) that cause the need for ground protection against flux and erosion by using filtration geotextile. The smallest value of the stability coefficient obtained using the ‘Fellenius’ method was Fs l.439 1.2 . The exact analysis of filtration conditions and stability allowed for the undertaking of solutionsensuring the safety for the structure.